Determination Of A Low Glycaemic Index Pre-Exercise Rice-Based Mixed Meal And Its Effect On Endurance Exercise Performance In A Heat Stress Environment Zaini Binti - Bahari, Zaini (2025)
The pre-exercise low glycaemic index (lgi) meal has been shown to enhance endurance exercise performance in a thermoneutral environment. Limited information is currently available on the lgi mixed meal based on the asian-based diet. Furthermore, the contribution of this asian-based lgi mixed meal in enhancing endurance exercise performance in a heat stress environment has yet to be widely examined. Based on this lack of information relating to the asian-based mixed meal on endurance exercise performance in a heat stress environment, a series of studies were conducted. The first study was conducted to identify the dietary intakes of malaysian endurance athletes (n = 85) and the selection of foods that the athletes commonly consumed. The second study was carried out to determine the glycaemic index (gi) value of rice-based mixed meals, whereas the menu was based on the foods the athletes commonly consumed.